DILEMA IMPLEMENTASI KURIKULUM MERDEKA DI SMP: MENGURAI BENANG KUSUT PROBLEMATIKA DALAM PEMBELAJARAN MATEMATIKA - Dharsono, Farhan Maulana; Fadjarajani, Siti; Mulya, Gumilar; Marwan, Iis (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
The implementation of the Merdeka Belajar Curriculum (KMB) in lower secondary mathematics education aims to transform the educational paradigm towards critical thinking and constructivism. However, the reality on the ground shows a gap between policy vision and classroom practice. This study uses a descriptive literature review method to identify and analyze various problems in the implementation of KMB in mathematics. The results of the study indicate four main pillars of obstacles: (1) limited adaptive resources and teaching aids, (2) low professional readiness of teachers in their roles as facilitators of differentiated learning, (3) students' psychological resistance to independent learning, and (4) inconsistency in conceptual understanding among stakeholders. These findings emphasize that the success of KMB requires holistic synergy through the optimization of local resources, strengthening teacher competence in Learning Communities, and psychological interventions to build a participatory learning culture. The conclusion of this study highlights the importance of systematic mitigation strategies to ensure that KMB functions optimally in improving the quality of mathematics education sustainably.